Answer:
The Line integral is π/2.
Step-by-step explanation:
We have to find a funtion f such that its gradient is (ycos(xy), x(cos(xy)-ze^(yz), -ye^(yz)). In other words:
![f_x = ycos(xy)](https://tex.z-dn.net/?f=%20f_x%20%3D%20ycos%28xy%29%20)
![f_y = xcos(xy) - ze^{yz}](https://tex.z-dn.net/?f=%20f_y%20%3D%20xcos%28xy%29%20-%20ze%5E%7Byz%7D%20)
![f_z = -ye^{yz}](https://tex.z-dn.net/?f=%20f_z%20%3D%20-ye%5E%7Byz%7D)
we can find the value of f using integration over each separate, variable. For example, if we integrate ycos(x,y) over the x variable (assuming y and z as constants), we should obtain any function like f plus a function h(y,z). We will use the substitution method. We call u(x) = xy. The derivate of u (in respect to x) is y, hence
(Remember that c is treated like a constant just for the x-variable).
This means that f(x,y,z) = sen(x,y)+C(y,z). The derivate of f respect to the y-variable is xcos(xy) + d/dy (C(y,z)) = xcos(x,y) - ye^{yz}. Then, the derivate of C respect to y is -ze^{yz}. To obtain C, we can integrate that expression over the y-variable using again the substitution method, this time calling u(y) = yz, and du = zdy.
![\int {-ye^{yz}} \, dy = \int {-e^{u} \, dy} = -e^u +K = -e^{yz} + K(z)](https://tex.z-dn.net/?f=%5Cint%20%7B-ye%5E%7Byz%7D%7D%20%5C%2C%20dy%20%3D%20%5Cint%20%7B-e%5E%7Bu%7D%20%5C%2C%20dy%7D%20%3D%20-e%5Eu%20%2BK%20%3D%20-e%5E%7Byz%7D%20%2B%20K%28z%29)
Where, again, the constant of integration depends on Z.
As a result,
![f(x,y,z) = cos(xy) - e^{yz} + K(z)](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%20%3D%20cos%28xy%29%20-%20e%5E%7Byz%7D%20%2B%20K%28z%29%20)
if we derivate f over z, we obtain
![f_z(x,y,z) = -ye^{yz} + d/dz K(z)](https://tex.z-dn.net/?f=%20f_z%28x%2Cy%2Cz%29%20%3D%20-ye%5E%7Byz%7D%20%2B%20d%2Fdz%20K%28z%29%20)
That should be equal to -ye^(yz), hence the derivate of K(z) is 0 and, as a consecuence, K can be any constant. We can take K = 0. We obtain, therefore, that f(x,y,z) = cos(xy) - e^(yz)
The endpoints of the curve are r(0) = (0,0,1) and r(1) = (1,π/2,0). FOr the Fundamental Theorem for Line integrals, the integral of the gradient of f over C is f(c(1)) - f(c(0)) = f((0,0,1)) - f((1,π/2,0)) = (cos(0)-0e^(0))-(cos(π/2)-π/2e⁰) = 0-(-π/2) = π/2.